PENGARUH PEMBERIAN KINETIN TERHADAP INDUKSI TUNAS PADA EKSPLAN STEVIA (Stevia rebaudiana B.) MELALUI KULTUR JARINGAN - YACHYA, ARIF; Nurokhman, Amin; As’ad, Zuhdi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2024)
The stevia plant (Stevia rebaudiana B.) is found in the United States, and is often used as a mixture in drinks. In Indonesia, cultivation of stevia began in 1977 in West Java and Central Java. The natural sweetener content with low calories makes stevia a solution for diabetes sufferers. Conventional cultivation takes a long time and depends on soil conditions, climate and variety. Tissue culture is used for plant propagation in a short time, free of pests and diseases, and does not depend on the season. Growth Regulators (ZPT) such as kinetin are used to accelerate shoot growth. The tissue culture media used is Murashige Skoog (MS). This study aims to examine the effect of kinetin on shoot induction in stevia explants through tissue culture, with explants in the form of leaf petioles. This study used a Completely Randomized Design (CRD) with kinetin concentrations of 1 ppm, 2 ppm, 3 ppm and 4 ppm. The results of the research showed that all kinetin treatments on leaf petiole mother explants were able to form shoots with an average percentage of 100%. But it didn't show any influence.